Determination of Uranium, Plutonium, Cesium and Europium Isotopes in Nuclear Fuel Claddings by Isotope Dilution Mass Spectrometry and g-Ray Spectrometry - Suk Kim, Jung; Shin Jeon, Young; Park, Yang-Soon; Il Park, Jai; Joon Park, Yong (Asian Journal of Chemistry, 2014)
Isotope dilution mass spectrometric (IDMS) and g-ray spectrometric (GRS) methods have been used for the determination of uranium, plutonium, cesium and europium isotopes in cladding from pressurized water reactor nuclear fuel irradiated in a power reactor. A dissolution of cladding samples was performed through a two-step procedure, washing with 8 M HNO3 at 90 ºC and dissolving with 2 M HF at 25 ºC followed by dissolving with aqua regia at 90 ºC. After the dissolution procedure, the chemical composition of insoluble residue (< 2 wt. %) was identified using a g-ray spectrometry. The isotopic compositions and their contents of uranium and plutonium and the activities of cesium and europium isotopes found in the dissolving and washing solutions of the cladding specimen from high burnup nuclear fuel, were compared with those found in a dissolving and washing solutions of the cladding specimen from low burnup nuclear fuel.